Effect of oral sugar solution for reducing pain in infants underwent diphtheria, pertussis, tetanus (DPT) im- munization: a randomized, double-blind controlled trial - Arief Priambodo; Madarina Julia; Djauhar Ismail (Indonesian Pediatric Society, 2008)
Background Infants are often subjected to painful procedures suchas diphtheria, pertussis, tetanus (DTP) immunization. Despiteits negative effects, pain in infants has not got enough attention.Sweet oral solution has analgesic effect.Objective To determine whether oral sugar solution can reducethe duration of crying in infants who got DTP immunization.Methods This was a randomized, double-blind controlled trialperformed at Growth and Development Clinic of Dr. SardjitoGeneral Hospital and two Primary Health Centers in Yogyakarta.Study subjects were 4-6 month-old infants who got the 3 rd DTPimmunization. Subjects were randomly allocated to receive 2 ml75% oral sugar solution (intervention group) or 2 ml drinkingwater (placebo) just before the immunization. Crying was recordedfrom just before the injection until 3 minutes after.Results Eighty-six subjects were enrolled; 42 subjects receivedsugar solution and 44 subjects received placebo. Sugar solutionreduced the median duration of first cry about 38 seconds or 32%(P=0.03) and reduced the median duration of total crying about35 seconds or 24% (P=0.02).Conclusion Administration of 2 ml 75% oral sugar solution canalleviate pain associated with DTP immunization as shown byreduced duration of crying.